2010
DOI: 10.1093/sleep/33.8.1075
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Craniofacial Structures and Obesity in Caucasian and Chinese Patients with Obstructive Sleep Apnea

Abstract: Craniofacial factors and obesity contribute differentially to OSA in Caucasian and Chinese patients. For the same degree of OSA severity, Caucasians were more overweight, whereas Chinese exhibited more craniofacial bony restriction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
199
2
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 269 publications
(218 citation statements)
references
References 25 publications
8
199
2
9
Order By: Relevance
“…The increased muscular stiffness of the soft palate suggests that its tissues undergo morphological and functional changes, supported by the findings of the uvular and soft palate muscles in snoring [40]. The changes thought to be due to varying combinations of anatomical and neuromuscular factors resulting in airway changes [26]. In our sample, there is no pathological findings or underlying cause for obstruction were detected except the changing in the measurements.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The increased muscular stiffness of the soft palate suggests that its tissues undergo morphological and functional changes, supported by the findings of the uvular and soft palate muscles in snoring [40]. The changes thought to be due to varying combinations of anatomical and neuromuscular factors resulting in airway changes [26]. In our sample, there is no pathological findings or underlying cause for obstruction were detected except the changing in the measurements.…”
Section: Discussionsupporting
confidence: 80%
“…Our sample have less measurement and not reach the cutoff point of obstruction diagnosis, but it differ from non-snoring; it means the measurements increased by 43 mm from 109.4 mm for patients measurements ranged from 84.5 -126 mm, may consider as snoring complain but not broaden to be diagnosed as obstruction sleep apnea. We justify this findings is that to be anatomical variations between different studied ethnic groups [26] [33]. Despite the clear association between snoring underlying causes and obesity, the mechanisms behind this relationship is not yet fully understood.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…30 Also, a previous study showed that obstructive sleep apnea syndrome developed at a lower body mass index level in Asian populations than in Western populations because of Asian cephalometric characteristics such as a smaller maxilla and mandible, retrognathia, and a shorter and steeper anterior cranial base. 31 Finally, all subjects in our study underwent open renal surgery. Because patients undergoing laparoscopic-or robotic-assisted renal surgery were excluded, the effect of pneumoperitoneum on tube displacement and change in cuff pressure was not investigated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…This variation also points towards the possibility of an osteogenic etiology of Obstructive sleep apnea [6] . Some studies like the one from China found that craniofacial structures and obesity contributed differentially to Obstructive sleep apnea in two ethnic groups [7] . The joint committee (JNC-7) on prevention, detection, evaluation and treatment of high blood pressure recognizes Obstructive sleep apnea as a significant risk factor for hypertension [8] .…”
Section: Introductionmentioning
confidence: 99%